2018
DOI: 10.3892/ijmm.2018.3383
|View full text |Cite
|
Sign up to set email alerts
|

Role of exosomes and exosomal microRNAs in hepatocellular carcinoma: Potential in diagnosis and antitumour treatments (Review)

Abstract: Communication between hepatocellular carcinoma (HCC) cells and their environment is essential for the development and progression of HCC. Exosomes, which are microvesicles secreted by a number of cell types, are carriers of intercellular information and regulate the tumour microenvironment. Studies have demonstrated that exosomes are involved in the communication between HCC cells, endothelial cells and stem cells, and that they serve important roles in the metastasis and invasion, immune evasion and immunothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 76 publications
3
52
0
Order By: Relevance
“…Recently, many studies have been performed on serum exo-miRs to detect novel biomarkers for HCC [25][26][27]. However, the diagnostic efficiencies of the previously evaluated serum exo-miRs have not been satisfactory for clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies have been performed on serum exo-miRs to detect novel biomarkers for HCC [25][26][27]. However, the diagnostic efficiencies of the previously evaluated serum exo-miRs have not been satisfactory for clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs have been reported to play pivotal roles in regulating development, diagnosis, and antitumor treatments of HCC 21 . In this study, we found that miR-196a and miR-196b expressions were enhanced in HCC tissues and cells, which is also in agreement with previous efforts 10, 11 .…”
Section: Discussionmentioning
confidence: 99%
“…In human beings, the majority of miRNAs are located in introns or non-coding mRNA transcripts of protein-coding genes, while the remaining miRNAs are distant from the transcripts in the genome, such as the exons of non-coding mRNA genes, or 3' UTR of mRNA genes, or other miRNAs genes [3]. In recent years, more and more studies have proved that miRNAs play important roles in a variety of cancer progression, such as respiratory cancers [4], digestive system cancers [5,6], neurological system cancers [7], genitourinary cancers [8] and vascular cancers [9]. miRNAs regulate the proliferation, differentiation, invasion, apoptosis and metastasis process of cancer cells in the form of oncogenes or tumor suppressor genes [10,11].It is worth noting that miRNAs and their target mRNA play synergistic network roles in cancer progression, and the analyses of miRNA expressions have identified potential markers for the diagnosis, prognosis and treatment of cancer patients [12,13].In these respects, more and more studies have confirmed…”
Section: Introductionmentioning
confidence: 99%